2015
DOI: 10.1007/s11999-014-3762-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Lumbar Discectomy in Elite Athletes: The Need for High-level Evidence

Abstract: Background Although lumbar discectomy for treatment of lumbar disc herniation in the general population generally improves patients' pain, function, and validated outcomes scores, results of treatment in elite athletes may differ because of the unique performance demands required of competitive athletes. Questions/purposes We performed a systematic review to answer the following questions: (1) What proportion of athletes return to play after lumbar discectomy, and what is the effect of sport? (2) What is the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Studies have found similar results when comparing microdiscectomy to nonsurgical treatments in elite NFL players [11]. Recovery from lumbar discectomy in elite athletes has been reported to range from 2.8 to 8.7 months with an average career length of 2.6 to 4.8 years [63].…”
Section: Main Textmentioning
confidence: 90%
“…Studies have found similar results when comparing microdiscectomy to nonsurgical treatments in elite NFL players [11]. Recovery from lumbar discectomy in elite athletes has been reported to range from 2.8 to 8.7 months with an average career length of 2.6 to 4.8 years [63].…”
Section: Main Textmentioning
confidence: 90%
“…In a study of 137 National Football League (a difference in outcome) players with LDH, surgical treatment led to a significantly longer career and higher return to play rate than those treated non-operatively ((37 months vs. 24 months, respectively; P = 03 ) and (36 games vs. 20 games, respectively; P = 002)) ( 10 ). Similarly, Schroeder et al reported 85% RTP rates in 87 hockey players with no significant difference in rates or outcomes between the surgical and nonsurgical cohorts, an outcome found in major league baseball players as well ( 28 , 35 ). These studies conclude that although a diagnosis of lumbar disc herniation has career-ending potential, most players are able to return to play and generate excellent performance-based outcomes, even if surgery is required ( 10 ).…”
Section: Lumbar Disc Herniationmentioning
confidence: 95%
“…For example, American football players have a significantly lower rate of return-to-play than baseball athletes, which could be explained by the physical nature of the respective sports ( 31 ). Furthermore, comparative studies show that a lumbar discectomy may lead to a shorter career in baseball players compared to non-operative treatment (233 versus 342 games, respectively; P = 0.08), suggesting that physical demands unique to this sport may lead to a difference in outcome ( 35 ). While the etiology of this effect has yet to be proven, some authors have postulated that the twisting nature of some sports may predispose players to chronic problems after disc surgery.…”
Section: Lumbar Disc Herniationmentioning
confidence: 99%
“…The average age of a professional NHL hockey player is 25.5 ± 4.4 years of age. 3 Because this injury took place in a 39-year-old player, there are physiological changes that must be accounted for that are not common in younger athletes including arthritic changes in the bone and a decrease in the fluid in the intervertebral discs. After 19 years of professional hockey, the patient has experienced numerous stresses on their lumbar spine compared to a rookie.…”
Section: Uniquenessmentioning
confidence: 99%